Safety and immunogenicity of human rabies vaccine for the Chinese population after PEP: A systematic review and meta-analysis. Issue 32 (30th July 2022) - Wang, Lei; Zhang, Jing; Meng, Shengli; Ge, Lingrui; You, Yuanyuan; Xu, Qi; Wang, Hongbo; Yang, Jing; Wang, Shuai; Wu, Haofei
Abstract: Aim: To evaluate the safety and immunogenicity of rabies vaccine for human use after post-exposure in China. Methods: A systematic search was performed from PubMed, EMBASE, CNKI and Cochrane Library database, supplemented by manual retrieval. According to the inclusion and exclusion criteria, a meta -analysis was performed using Stata 16.0 software after independent literature screening, data extraction and quality assessment by two evaluators. Results: A total of 32 studies were included. It was found that rabies vaccination after PEP could induce the body to produce sufficient RVNA. Both Essen and Zagreb regimens showed good immunogenicity, with no significant difference in systemic events and local events after PEP, but a relatively high incidence of local and systemic events after PEP under the Zagreb regimen. Conclusion: For the Chinese population, rabies vaccination after PEP has shown relatively a good immune efficacy and acceptable safety for preventing human rabies. The survey also found that the Zagreb regimen was comparable to the Essen regimen in terms of rabies prophylaxis with an acceptable safety profile.